Association between the use of physical restraint and functional decline among older inpatients admitted with pneumonia in an acute care hospital: A retrospective cohort study. (May 2021) - Soeno, Shoko; Takada, Toshihiko; Takeshima, Taro; Kaneyama, Mirei; Sagawa, Manami; Hayashi, Michio; Miyashita, Jun; Azuma, Teruhisa; Fukuma, Shingo; Fukuhara, Shunichi
Highlights: Use of physical restraints is associated with functional decline in older inpatients. This study quantified restraint frequency effects on ADL in an acute care setting. Katz scores would decrease by 1.0 if a patient were restrained for 13.9 days. Abstract: Aim: This study was conducted to investigate the association between the use of physical restraint and functional decline in older inpatients admitted with pneumonia in an acute care setting. Although several adverse effects related to restraint use have been reported, few researchers have examined this subject in acute care settings. Methods: This retrospective cohort study was conducted at a 471-bed, acute care hospital in Japan. Patients 65 years old and older who were admitted with pneumonia between April 2015 and September 2017 were included. The use of restraints (belts and/or mittens) was recorded for every 8-hour shift. The number of shifts during which each patient was restrained was used as an explanatory variable. The primary outcome was the Katz ADL score at discharge. We used multiple linear regression analysis to adjust for confounding factors. Results: Of 403 patients, 94 required physical restraints. The mean age was 84.5 years (standard deviation [SD] 8.2); 44.4% were women. The mean Katz score on admission was 2.7 (SD 2.4). For multiple linear regression analysis, the coefficient of the number of restraints used was -0.024 (95% confidence interval: -0.044, -0.003, p = .022). Consequently, the restraint use for 13.9 days was associated with the decrease in the Katz score by 1.0. Conclusions: Results suggest that physical restraint use is associated with functional decline among older inpatients admitted with pneumonia in acute care settings.